2021
DOI: 10.1128/jcm.00406-21
|View full text |Cite
|
Sign up to set email alerts
|

The Simple One-Step (SOS) Stool Processing Method for Use with the Xpert MTB/RIF Assay for a Child-Friendly Diagnosis of Tuberculosis Closer to the Point of Care

Abstract: Young children cannot easily produce sputum for diagnosis of pulmonary tuberculosis. Alternatively, Mycobacterium tuberculosis complex (MTB) bacilli can be detected in stool by using the Xpert MTB/RIF (Ultra) assay (Xpert). Published stool processing methods contain somewhat complex procedures and additional supplies. The aim of this study was to develop a simple one step (SOS) stool processing method, based on gravity sedimentation only, similar to sputum Xpert testing for the detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 22 publications
(47 reference statements)
1
40
1
Order By: Relevance
“…This shows that there is a lack of standardized stool preparation and testing protocols and warrants the optimization and standardization of the stool processing methods that can be used at the decentralized level. The KNCV Tuberculosis Foundation (KNCV) and Ethiopian Public Health Institute (EPHI) developed the Simple One-Step (SOS) stool processing method, which can be applied in any GeneXpert laboratory (8).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This shows that there is a lack of standardized stool preparation and testing protocols and warrants the optimization and standardization of the stool processing methods that can be used at the decentralized level. The KNCV Tuberculosis Foundation (KNCV) and Ethiopian Public Health Institute (EPHI) developed the Simple One-Step (SOS) stool processing method, which can be applied in any GeneXpert laboratory (8).…”
Section: Introductionmentioning
confidence: 99%
“…The SOS method has shown to be successful, with a low rate of unsuccessful results reported, in a demonstration study conducted in Ethiopia, in which multiple laboratories were involved (8). Furthermore, a head-to-head comparison study, in which the SOS method is compared to other stool processing methods showed similar sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations